Premedication and induction of anaesthesia in paediatric patients - Dave, Nandini (Indian journal of anaesthesia, 2019)
Perioperative anxiety has been associated with adverse clinical outcomes such as emergence delirium, increased analgesic requirements and negative postoperative behavioural changes such as sleep disturbance, separation anxiety, eating problems and new-onset enuresis. Predictors of preoperative anxiety have been identified, and these include, among other factors, the age and temperament of the child. Any plan for anaesthetic induction in a child must take into account these factors. The anaesthetic plan must be individualised for special situations, for example, the child with behavioural disorder or at risk of aspiration. This article details the pharmacological and nonpharmacological methods to minimise preoperative anxiety and the techniques of anaesthetic induction in infants and children undergoing surgery. The benefits and limitations of inhalational and intravenous induction and the current status of rapid sequence induction in children are discussed. MEDLINE database was searched for this narrative review using the keywords including preoperative anxiety, child, premedication, paediatric and anaesthetic induction. Search was restricted to articles in English, but without any publication date restrictions.